Batteries: Nano‐Copper‐Assisted Immobilization of Sulfur in High‐Surface‐Area Mesoporous Carbon Cathodes for Room Temperature Na‐S Batteries (Adv. Energy Mater. 12/2014). Issue 12 (August 2014) - Zheng, Shiyou; Han, Pan; Han, Zhuo; Li, Peng; Zhang, Huijuan; Yang, Junhe
<x xml:space="preserve">Abstract</x> In article number 1400226, Shiyou Zheng, Junhe Yang, and co‐workers report a novel, in situ, sulfur‐reducing and intercalating graphite oxide strategy to fabricate a high S loading graphite‐S composite cathode with superior electrochemical performance. The reduced graphite oxide can effectively stabilize the intercalated small molecule S2 through both physical confinement and chemical interaction. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>